2022
DOI: 10.1002/solr.202200623
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum‐Processed Perovskite Solar Cells: Materials and Methods

Abstract: Perovskite solar cells (PSCs) based on inexpensive organic−inorganic hybrid semiconductors are considered a promising next‐generation solar cell technology. For PSC commercialization, the further development of efficient and scalable fabrication methods is essential. To date, solution‐based methods have been widely studied due to simplicity and cost‐effectiveness. Despite the advantages, it is still necessary for developing vacuum‐based methods as the alternative methods due to reproducibility and uniformity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…There have been many studies reported on scalable perovskite films using blade coating. [ 57 ] Controlling the perovskite film's crystallization in this procedure is more difficult because the solvent evaporates very slowly. Consequently, it is quite challenging to create a dense, consistent film during the process.…”
Section: Scalable Deposition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies reported on scalable perovskite films using blade coating. [ 57 ] Controlling the perovskite film's crystallization in this procedure is more difficult because the solvent evaporates very slowly. Consequently, it is quite challenging to create a dense, consistent film during the process.…”
Section: Scalable Deposition Methodsmentioning
confidence: 99%
“…Thickness and morphology of the films are investigated by the meniscuses’ shapes, the coating speed, the solution feed rate, etc. [ 57 ] Slot‐die printing is broadly used techniques for scaling up PSCs and PSMs. This may produce homogenous perovskite films across greater regions with adequate optimization and control, which enhances the performance of PSCs.…”
Section: Scalable Deposition Methodsmentioning
confidence: 99%
“…The difference in PCE between unit cell and module increased with an increase in the active area, resulting in the largest gap of ≈30% at an active area of over 100 cm 2 . [ 12,13 ]…”
Section: High Efficiency Perovskite Solar Modulesmentioning
confidence: 99%
“…Perovskite precursor engineering is to design the precursor solution suitably for each coating process, and it is the most important factor for obtaining scalable perovskite film with high crystallinity, reproducibility, and uniformity over a large area. [ 12,40 ] In this section, we review the research progress on solution processes for fabricating PSMs with an active area above 10 cm 2 over the last three years, and discuss the essential factors for precursor engineering and the advanced processes.…”
Section: High Efficiency Perovskite Solar Modulesmentioning
confidence: 99%
“…The vacuum-processed PSC fabrication method through codeposition, sequential deposition, or single-source deposition of precursor materials can help fabricate a uniform and homogeneous film on a large area with better control of film thickness regardless of the substrates and fabrication condition. 7,8 Moreover, better reproducibility with a solventfree process makes vacuum-based methods suitable for upscale and commercialization by including a solar module and tandem device. 9−12 The coevaporation method is the most popular vacuum-processed method that simultaneously sublimates multiple precursors onto substrates in a high vacuum chamber.…”
Section: ■ Introductionmentioning
confidence: 99%